As representações do amor legítimo e ilegítimo na retórica de ovídio: os exempla mitológicos e cotidianos das normas coletivas às matronas na República e transição ao Império Romano (séculos I A.E.C – I D.E.C.) - ARAUJO, Alexandro Almeida Lima (2023)
This work has as an approach the thinking about the feminine in ancient Rome, more precisely about the Roman matrons. These were women who belonged to the Roman aristocracy and there were attempts to control their bodies by the male. Control and surveillance over the materfamilias, or the nubile young woman, often took place through the dissemination of the rules of the Mores Maiorvm, based, therefore, on the traditional values of ancient times. The diffusion of these norms could be found in Latin rhetoric, such as, for example, in the work Fasti, by a rhetor called Ovid, in which, by exploring the religious festivities of the Roman calendar and their myths in the montage of the referred work, the rhetorician made, discursively, with the establishment of a male domination, in which the man was the active subject and the woman would only be passive. This social hierarchization was quite metaphorized through the roles of each one in sexual intercourse, that is, the male is the virile being, because he is responsible for the hardened phallus and penetration, and the woman would be the one who always receives, or “guards”, almost “inertly”, with his genital organ, this phallus, or rather, the male vir, which symbolizes the virility of the Roman man. This can be proven by the fact that Ovid will seek mythological examples to support this imposition, in which male deities will be an example to men, and female deities will be constructed to become an example to women. Let's explain better, the qualities that gods and goddesses possessed, that is, their archetypes, would become models for both men and women on earth to mirror these virtues and reproduce them on the non-divine plane. For example, this was the case of Jove and his virility, in which the god is the representation of the imposition of uir on the feminine, or even in the case of Juno, goddess who presided over childbirth, in which matrons should honor her so that their children were born alive and had a peaceful delivery. Or Vesta, virgin goddess, who demonstrated that noble women should be chaste, largely because of the imposed rule of legitimate descent that women should give to gens of paternal power. Or Minerva who was supposed to teach the young women to weave and spin wool, in effect, a domestic activity. In this way, we will be able to perceive the most varied relationships, whether social or in the field of love itself, considered legitimate and illegitimate, in which the first were exalted and praised by the rhetor, and the second were potentially censored. To do so, our focus will be the 1st century before the Common Era and the 1st century after the Common Era, the writing period of our documentary source, however, in many cases, it will be necessary to go back and forth paths, in which “other” temporalities will be approached by the connected histories, since the “Ovidian myths” tend to turn to the mythical reports of “other” societies, such as, for example, the Greek, the Etruscan, the Sabine, the Egyptian, etc. were in constant contact.